2017
DOI: 10.1159/000455825
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Arrest Triggered by Coadministration of Fluconazole and Amiodarone

Abstract: Fluconazole for fungal infections and amiodarone for arrhythmia are commonly prescribed medications, and coadministration of such medications is sometimes inevitable in clinical practice. However, both medications have been associated with prolonged QTc intervals and subsequent arrhythmias, which are sometimes fatal. We present the case of a 75-year-old man with sudden cardiac arrest triggered by coadministration of fluconazole and amiodarone, which raises the need for caution regarding coadministration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Anti-arrhythmics are another group of drugs frequently used among cardiac patients. Wang et al in 2017 reported a case of sudden cardiac arrest in a patient treated simultaneously with uconazole and amiodarone [29]. Another reported life-threatening side effect of multiple therapies in a patient taking atorvastatin, amiodarone, and uconazole was rhabdomyolysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-arrhythmics are another group of drugs frequently used among cardiac patients. Wang et al in 2017 reported a case of sudden cardiac arrest in a patient treated simultaneously with uconazole and amiodarone [29]. Another reported life-threatening side effect of multiple therapies in a patient taking atorvastatin, amiodarone, and uconazole was rhabdomyolysis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda tespit edilen etkileşimlerden sadece klaritromisin-amiodaron kombinasyonu "X" yani "birlikte kullanımından kaçınılması gereken ilaçlar" düzeyinde olup, klaritromisin tedavisi değiştirilmiştir. Klaritromisin gibi hem CYP3A4 inhibitorü olup hem de QT uzamasına yol açan flukonazolun da amiodaron ile birlikte kullanımı sonucu bir hastada ani kardiyak arrest bildirilmiş olup, bu ilaçların potansiyel etkileşim düzeyi "D" yani "tedavide değişikliğe gidilmesi gereken etkileşim" olarak belirlenmiştir (8,26). Çalışmamızda flukonazol-amiodaron kullanımı olan 2 hastada flukonazol tedavisinin değiştirilmesi önerilmiş olup, hekimler tarafından kabul edilmiştir.…”
Section: Discussionunclassified